Quality of life, its factors, and sociodemographic characteristics of Polish women with lipedema - Joanna E. Dudek; Wojciech Białaszek; Marcin Gabriel (BMC, 2021)
Abstract Background Lipedema is a type of subcutaneous adipose tissue disorder that affects mainly women. Its main symptom is bilateral fat accumulation on the extremities with associated pain in the affected areas. Despite growing interest in lipedema among patients and medical health professionals, lipedema is still often misdiagnosed, misunderstood, and mistreated. To promote better understanding of lipedema, we aimed to investigate factors related to the quality of life and describe selected sociodemographic and clinical characteristics of women with lipedema in Poland. Methods We conducted a cross-sectional online survey that was completed by 98 women with lipedema. The participants responded to questionnaires regarding quality of life, sociodemographic and clinical characteristics, and depression symptom severity. Results The participants reported low quality of life and high severity of depressive symptoms. The more severe the symptoms related to pain, heaviness, and swelling, the lower the quality of life. Further analyses showed that depression severity mediated this relationship. Conclusions The current study provides initial information on screening questions, lipedema symptoms, and comorbidities, pointing to the areas needing in-depth investigation. Further steps to improve quality of life in women with lipedema and to reduce health costs should include the education of medical health professionals, using diagnostic tools that allow for differentiation among diagnoses and precise health risk assessment, and creating Polish treatment guidelines for lipedema.